Premature Sign-Off of Audit Procedure - Maryam Hafidhatul Izzah; Nujmatul Laily (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2020)
This research aims at testing influence of time pressure on premature sign-off of audit procedure with professional commitment as the moderating variable. This research uses questionnaire to collect the data. Meanwhile, the population in this research are all independent auditors working for Public Accountant Offices in Malang, Indonesia. Amounting to a total of 50 auditors are used as the sample in this research. The sample in this this research is taken using purposive sampling. The result indicates that time pressure has a positive influence on premature sign-off of audit procedure. This means the greater the time pressure the auditors are having, the more likely the auditors to be involved in premature sign-off of audit procedure practice, and vice versa. The second finding is that professional commitment weakens the influence of time pressure on premature sign-off of audit procedure. This means if an auditor is faced with high time pressure yet he/she possesses high professional commitment then the possibility of this auditor to get involved in premature sign-off of audit procedure practice is lower, and vice versa.